The Strategic Role of Mosques in Empowering the Community's Economy: A Case Study of the Bintaro Jaya Grand Mosque - Khusnaini Khusnaini; Nur Farida Liyana; Nur Aisyah Kustiani (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to explore the strategic role of mosques in empowering the Muslim community’s economy, with a case study at Masjid Raya Bintaro Jaya (MRBJ) in the urban area of South Tangerang. Using a descriptive qualitative approach and single case study design, data were collected through in-depth interviews, participant observation, and documentation of mosque-based economic activities. The findings reveal that MRBJ has successfully implemented structured economic programs such as interest-free microloans (bank infaq), small business carts (gerobak berkah), MSME training, and the development of a commercial halal zone. Supporting factors include community trust, ZIS fund potential, and strategic partnerships. Challenges include low financial literacy and default risks. This study concludes that mosques can act as effective agents of economic empowerment through institutional strengthening, cross-sectoral collaboration, and the development of a measurable and sustainable empowerment roadmap.